Making Sense of the City: Public Spaces in the Philippines - Barbaza, Remmon E (Archīum Ateneo, 2019)
Making sense of the City is a collection of essays from scholars in the humanities and the social sciences examining the city within the Philippine context. With Metro Manila bursting at the seams, as tensions continue to intensify and more intractable problems arise than those that are being solved, it becomes a matter of survival for all stakeholders to come together and shape the future of the city.